Parenting Patterns of URBAN Adolescents & Bullying Behavior - Syamsiah Badruddin; Edy Wahono (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2021)
The phenomenon that occurs at SMA Negeri 51 East Jakarta is that parents verbally abuse their children, among others, such as violence carried out through hurtful words. These hurtful words usually mean harassing children's abilities, considering children as a source of bad luck, being shouted at too loudly, looking down on children, venting anger at children when children make the same mistakes as parents, and comparing children. This research resulted in several conclusions including: 1. The majority of students have the characteristics of a democratic parenting style and there is no major influence on the perpetrators with parental parenting, the intensity of bullying at SMA Negeri 51 East Jakarta is mild, 2. What causes verbal violence against children against bullying behavior is the pattern of friends or the surrounding environment, prevention of verbal violence for families must use relaxed and comfortable interactions by accompanying what steps will be taken next 3. Application of discipline in the family, socialization of moral teachings and Social norms, namely harmony and independence, must also be polite to elders.